Acting as Autonomous and Complementary Partners. Conflictual Cooperation in Quebec’s Youth Concertation - Lefebvre, Marie (PARTECIPAZIONE E CONFLITTO, 2026)
In Quebec, “autonomous community organizations” are involved in the public health and social services network as autonomous and complementary partners. This partnership appears paradoxical, given that the movement claims an advocacy role vis-à-vis the state. It illustrates what Lamoureux (1994) describes as a relation of “conflictual cooperation” between the state and community organizations. How do actors navigate between cooperation with public institutions and conflict when necessary? Drawing on an ethnography conducted in two youth concertation tables, this article highlights the tensions inherent in conflictual cooperation and examines the conditions under which contestation can still be voiced by community actors. While concertation is framed as a site for collaboration, it also discourages community actors from “making things political” (Eliasoph and Lichterman 2018) by limiting their ability to challenge power relations with public institutions. The article argues that the absence of overt conflict in the performance of concertation often results less from alignment than from subtle control tactics – whether intentional or not – that channel and constrain dissent, although protest can still be reconfigured both backstage and outside concertation.